Um protótipo de reabilitação para a casa burguesa do Porto
Was it the fact of having been born and raised in Port that fueled the desire to structure areflection about her. It is particularly Lower the focus of my interest; this symbiosis betweenbeauty watching him in every detail, and the inertia of people, of bodies andcircumstances leading to the degradation of their heritage.Under this test becomes opportune finally think more deeply about thisproblematic. More than that, here we provide the conditions necessary to build aconceptual and architectural proposal that want to try to solve (in part) the problemhere we identified.At this intersection of interests assume the primary objective of the thesis designa rehabilitation prototype for the bourgeois house of Porto which, according to the analysis, isthe type most prominent housing Low Portuense. The aim of this prototypeensure across the board the rehabilitation and re occupation of these houses.It is therefore based on this principle, this intention, which we structure our study.At first, we seek to know the evolutionary path of the said bourgeois house fromits formation to the present day, touching the urban, social, and cultural are youinherent.After trying to understand the factors that led to its degradation, we know andwe analyze the strategy that has been employed by the responsible entity - Porto Vivo - inreverse sense. We questioned the feasibility of its action model, and moreimportant results. How involved in the built and respond to the interests ofpopulations. Whether the residents either of the wish to be.Forward with this study of the problem to the construction, the working processmonitors and embodies the prototype.We start by drawing an abstract model, a bourgeois house type, possessing allits fundamental characteristics. This model will form the basis, the space on whichfocuses our proposal.As conveyed in the academic path, we proceed with the base of intervention forcustomer knowledge and the development of a set of program requirements. Thisinvestigation subtract up the most relevant coordinates for the exercise of the project.Finally ended the construction of the problem with the development of the prototype - is deducedin the background, the embodiment of all assumptions, constraints and that the protagonistsThroughout the dissertation intersect.Expose the choices made, references and concepts that illustrate and touch issueswe always seem relevant in a project-oriented approach, and above all, from the perspective ofrehabilitation.This research aims to more than the design of a proposed exercise, find andexposing a point of view, an idea, a principle to recover this heritage, which has theto adjust to the current economic conjecture capacity and simultaneously respect thePlace memory.